2019
DOI: 10.1155/2019/7851251
|View full text |Cite
|
Sign up to set email alerts
|

Phylogenetic Analysis and Screening of Antimicrobial and Antiproliferative Activities of Culturable Bacteria Associated with the AscidianStyela clavafrom the Yellow Sea, China

Abstract: Over 1,000 compounds, including ecteinascidin-743 and didemnin B, have been isolated from ascidians, with most having bioactive properties such as antimicrobial, antitumor, and enzyme-inhibiting activities. In recent years, direct and indirect evidence has shown that some bioactive compounds isolated from ascidians are not produced by ascidians themselves but by their symbiotic microorganisms. Isolated culturable bacteria associated with ascidians and investigating their potential bioactivity are an important … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 97 publications
(100 reference statements)
1
13
0
Order By: Relevance
“…This contrasts with a recent review that analyzed bioactive ascidian-derived microbial compounds that showed higher rates of cytotoxicity (47%) than antimicrobial activity (31%) [16]. However, the vast potential of marine-derived microorganisms for discovery of novel antibiotics from ascidians and other marine invertebrates is known [69][70][71]. The fact that pathogenic Gram-negative bacteria were not inhibited by any of our tunic-associated microorganisms is in line with their general lesser susceptibility towards antibiotics due to their additional outer membrane [70,72].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…This contrasts with a recent review that analyzed bioactive ascidian-derived microbial compounds that showed higher rates of cytotoxicity (47%) than antimicrobial activity (31%) [16]. However, the vast potential of marine-derived microorganisms for discovery of novel antibiotics from ascidians and other marine invertebrates is known [69][70][71]. The fact that pathogenic Gram-negative bacteria were not inhibited by any of our tunic-associated microorganisms is in line with their general lesser susceptibility towards antibiotics due to their additional outer membrane [70,72].…”
Section: Discussionmentioning
confidence: 91%
“…The P. destructans isolate cultivated on medium CAG (CHT56-CAG) produced compounds of polyketide (55,(60)(61)(62) and terpenoid (56,65,67,70) origin (Figure 6 and Figure S6, Table S7). Accordingly, the two largest clusters in the FBMN, which consisted in total of 78 nodes, were putatively assigned to benzofuran-type polyketides and sesquiterpenoids.…”
Section: Extract Selection For Metabolomic Analyses and Ic 50 Determinationsmentioning
confidence: 99%
“…The antimicrobial assays included the so-called ESKAPE panel, drug-resistant bacterial pathogens that were categorized by the WHO as priority level 1 and 2 for the discovery of new antimicrobial agents [ 43 ]. Most extracts ( n = 65) exhibited activity against MRSA and/or E. faecium , but also anticancer ( n = 23) and antifungal ( n = 11) activities were observed ( Figure 3 , Table S2 ), exceeding bioactivity levels previously reported for cultivable bacteria associated with solitary ascidians [ 44 , 45 ]. The high rate of bioactivity observed in this study is in line with the excellent biodiscovery potential reported for tunicates and their microbial associates [ 11 , 13 , 42 ].…”
Section: Discussionmentioning
confidence: 77%
“…For example, Davies-Bolorunduro et al ( 2019) evaluated the anticancer activity of 32 actinomycetes strains against a panel of cancer cell lines and the isolates of genera Micromonospora and Streptomyces exhibited cytotoxicity with IC 50 values ranging from 0.03 to 4.4 mg/mL. Among other Phyla, some extracts of Halomonas and Bacillus have showed cytotoxicity with IC 50 < 50 µg/mL (Aboul-Ela et al, 2012;Sagar et al, 2013;Chen et al, 2019). It is noticeable that many secondary metabolites have been isolated from Bacillus, including peptides, terpenoids, polyketides, and isocumarins, however, a few marine Bacillus strains have been examined for pharmaceutical activities (Chen et al, 2019).…”
Section: Discussionmentioning
confidence: 99%